Analysis of Authentic Assessment Practices in Project-Based English Learning at the Secondary School Level - Monika Gultom (PT FORMOSA CENDEKIA GLOBAL, 2026)
Authentic assessment is a key component of project-based learning in English education, supporting the development of real-world communication, collaboration, creativity, and problem-solving skills. This qualitative study examines authentic assessment practices in project-based English learning at the secondary school level, focusing on teacher strategies, student experiences, and institutional support. Using purposive sampling, data were collected from two English teachers, eight students, and two curriculum staff in a secondary school in Jayapura through classroom observations, in-depth interviews, and document analysis, and analyzed thematically. The findings show that teachers employ authentic assessments such as performance-based rubrics, project portfolios, and presentations, but face challenges related to unclear assessment indicators, time limitations, and varying student readiness. The study concludes that while authentic assessment enhances 21st-century language competencies, its effectiveness depends on more consistent assessment design, clearer rubrics, and stronger school policy support, contributing to improved project-based learning and assessment models in English language education.